Case report Subcutaneous tumours as a harbinger of acute myeloid leukaemia recurrence - Dańczak-Pazdrowska, Aleksandra; Gil, Lidia; Sadowska, Anna; Knioła, Karolina; Komarnicki, Mieczysław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Skin lesions may suggest the recurrence of haematopoietic neoplasia. Cutaneous manifestations in leukaemia are divided into specific (leukaemia cutis, leukaemic vasculitis) and non-specific (leukaemids). Non-specific lesions may cause diagnostic difficulties due to their diversity. This paper presents two patients with acute myeloid leukaemia with skin lesions presented as tumours located in subcutaneous tissue. In both cases skin lesions precede the recurrence of the haematopoietic neoplasia.